Oral delivery of hydrophobic flavonoids and their incorporation into functional foods: Opportunities and challenges. (July 2022) - Premathilaka, Ruwanthi; Rashidinejad, Ali; Golding, Matt; Singh, Jaspreet
Abstract: Flavonoids have long been known for their healing powers in human ailments, with recent trends seeing these natural bioactive components increasingly extended into nutraceuticals and functional foods. Frequent intake of these compounds through diet arguably becomes a natural remedy for lowering the risk of non-communicable diseases. Hydrophobic flavonoids within the spectrum stand out, owing to their remarkable therapeutic effects including the capability of acting as a complementary approach to conventional therapy for COVID-19, suggested by novel research endeavors. However, various physicochemical aspects (e.g., low aqueous solubility, low permeability, and high oxidation susceptibility), as well as undesirable sensory attributes have hindered the direct incorporation of hydrophobic flavonoids into food matrices. Thus, the demand has risen for encapsulated/protected flavonoids that can maintain their original bioactivity during processing, storage, and gastrointestinal digestion. Taking the importance of these facts into consideration, the purpose of this critical review is to discuss different approaches for the encapsulation/delivery of hydrophobic flavonoids. Additionally, the strengths and weaknesses of delivery systems, recommendations to overcome possible challenges, the incorporation of encapsulated hydrophobic flavonoids into food materials, and the importance of considering toxicity aspects of the corresponding delivery systems have been discussed in detail. The influence of flavonoid systems on the overall physicochemical and organoleptic properties of functional food products has also been addressed, with a particular emphasis on the importance of food safety in this regard. Graphical abstract: Various aspects related to the oral delivery and encapsulation of hydrophobic flavonoids. Image 1 Highlights: The demand for the encapsulated/protected hydrophobic flavonoids has risen recently. Research on the application of hydrophobic flavonoids in the food industry is limited. In vivo behavior of encapsulation systems (release profile/absorption) is paramount. The use of nature-adapted delivery systems for flavonoids is a reliable option. Flavonoid delivery systems should be productive and economical at a large scale.